Determinación de la actividad biológica de metabolitos fitoquímicos acuosos extraídos de granos andinos - Larrea Martínez, Andrea Mishell (2023)
ABSTRAC Andean grains are among the foods that have been studied as a source of secondary metabolites with biological activity, which are also part of many family consumption and production systems in the Andean highlands. Through the present study it was possible to determine the presence of phytochemicals and their biological activity in the grains of sangorache (Amaranthus hybridus L.) and chocho (Lupinus mutabilis Sweet), the results were contrasted with the information published in the specialized scientific bibliography that gives account of the finding of phytochemicals with hemagglutinating, anticoagulant, antimicrobial and cytotoxic biological activity in grains in general and particularly in Andean grains. Among the results obtained, the presence of phytoagglutinins (lectins) was demonstrated in the two Andean grains studied, through the ability of their aqueous extracts to agglutinate human erythrocytes in a non-selective manner. In addition, they have significant anticoagulant activity by acting on plasmatic coagulation proteins of both the extrinsic and intrinsic pathways. Its antimicrobial activity revealed that both aqueous extracts obtained from lupine and sangorache inhibited the bacterial growth of the ATCC gram (+) strain of Staphylococcus aureus and the gram (-) strain of Proteus mirabilis. However, the extracts did not have any antibacterial effect against E. fecalis, E. coli and K. pneumoniae. Additionally, it was verified that only the aqueous extract of the chocho, presented a percentage of toxicity of 50% on the nauplii of Artemia salina in a concentration of 1000ug/ml in 24h. Keywords: biological activity, hemagglutinin, anticoagulant, antimicrobial, cytotoxic, phytochemicals, Andean grain